Global consensus from the PHITT consortium surrounding an interim chemotherapy guidance for the treatment of children with hepatoblastoma, hepatocellular neoplasm – not otherwise specified (HCN-NOS), hepatocellular carcinoma and fibrolamellar carcinoma after trial closure - Irene Schmid; Allison F. O’Neill; Kenichiro Watanabe; Isabelle Aerts; Sophie Branchereau; Penelope R. Brock; Madhumita Dandapani; Brice Fresneau; Jim Geller; Tomoro Hishiki; Danielle Ingham; Kathelijne Kraal; et al. (EJC Paediatric Oncology)
Malignant liver tumors affecting children and adolescents are rare. In order to adequately study liver tumors occurring in this patient population and establish a more uniform approach to therapy, the three primary liver tumor consortia, SIOPEL (mainly European), COG (mainly North American) and JCCG (Japan), in concert, designed an international prospective clinical trial [PHITT (Paediatric Hepatic International Tumour Trial)/COGAHEP1531/JPLT4 – to be referred to as PHITT from this point forth] for the study of hepatoblastoma and hepatocellular carcinoma in children and adolescents. Recruitment to PHITT has recently concluded. The major results from this trial will be published in the next 2–3 years, therefore in the interim, we sought to provide a consensus statement on evidence-based chemotherapy guidance for hepatoblastoma and hepatocellular carcinoma of all stages.